Strengthening Character Education through Multicultural Values-Based Civic Education (PPKn) to Promote Students’ Tolerance - Darmawati Darmawati; Andi Bahrun Syam; Hartati Malkab; Khair Khalis Syurkati (Journal La Edusci, 2026)
This study examines the role of multicultural values-based Civic Education (PPKn) in strengthening character education and promoting students’ tolerance. Grounded in the growing concern over declining tolerance among students in diverse societies, the research adopts a qualitative case study approach to explore how values are integrated and internalized within classroom practices. Data were collected through in-depth interviews, classroom observations, and document analysis involving PPKn teachers and students in a secondary school setting. The findings reveal that the implementation of multicultural values in PPKn is carried out through interactive and student-centered learning strategies, such as group discussions, case-based learning, and reflective activities, which encourage students to engage with diversity meaningfully. These practices contribute to the strengthening of character education by fostering values such as respect, empathy, responsibility, and social awareness. Furthermore, the study finds that students’ tolerance develops through continuous exposure to inclusive classroom environments, dialogic interactions, and collaborative learning experiences that promote mutual understanding and appreciation of differences. Teachers play a crucial role as facilitators and role models in guiding students toward positive attitudes and behaviors. The study concludes that multicultural values-based PPKn is an effective approach to integrating cognitive, affective, and behavioral dimensions of learning, thereby enhancing both character formation and tolerance among students. This research contributes to the discourse on character education and multicultural learning by highlighting the importance of contextual and value-oriented pedagogical practices in fostering inclusive and harmonious social relationships.